Assessing the efficacy of online applications in enhancing classroom teaching: A comprehensive evaluation of execution and effectiveness - Le, Thang Van; Tran, Tu Thi Cam; Nguyen, Hung Thanh; Nguyen, Tuan Van; Cao, Chinh Danh (Journal of Education and e-Learning Research, 2024)
This study explores the practical application of online applications in innovating the organization of teaching activities within public schools in Hue City, Vietnam. The research investigates the nuanced dynamics of execution and efficiency in using online applications across various teaching categories. The study employs a systematic approach to participant selection using stratified sampling based on geographical criteria to ensure representation from both the northern and southern regions of the city. A total of 192 teacher survey questionnaires were distributed focusing on the execution and efficiency of online applications in categories such as warm-up activities, knowledge building, review and consolidation, practice activities and testing and assessment. The commitment to data quality is demonstrated by the high response rate with 187 valid questionnaires collected (97.3% of the expected sample). Statistical analyses including mean scores, standard deviations and correlation coefficients were employed to provide a comprehensive evaluation of the current state of online application integration in teaching activities. The findings reveal varying levels of execution and efficiency across different teaching categories emphasizing the need for targeted improvement strategies. Strong positive correlations were observed in specific categories such as practice activities highlighting a consistent association between effective execution and efficiency. The study contributes valuable insights to the discourse on technology integration in education, offering recommendations for teachers, administrators and policymakers seeking to optimize the impact of online applications on teaching practices in the Vietnamese educational context.